Injectable hydrogel with anti-inflammatory and drainage functions for promoting anal fistula healing and preparation method of injectable hydrogel

By using GAA@CNT-g-PVBTMA hydrogel in the treatment of anal fistula, the problem of difficult filling and drainage balance in the prior art is solved, effective anti-inflammatory and healing of anal fistula is achieved, and the treatment effect of anal fistula is significantly improved.

CN119139560APending Publication Date: 2024-12-17THE FIFTH AFFILIATED HOSPITAL SUN YAT SEN UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411179939.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The prior art is difficult to achieve effective filling and drainage balance when treating anal fistula, resulting in low inflammatory complications and healing rates, and lack of methods that can remove inflammatory cytokines.

Method used

A GAA@CNT-g-PVBTMA hydrogel was developed by adding acrylate-N-succinimide acrylate, acrylated beta-cyclodextrin and grafted poly(vinylbenzyltrimethyl) to the gelatin solution ) carbon nanotubes form an injectable hydrogel with anti-inflammatory and drainage functions, and are prepared using thermal curing and mechanical crushing technology.

Benefits of technology

The hydrogel exhibits excellent anti-swelling properties and porous structure, can effectively fill the fistula and capture inflammatory cytokines, significantly reduce inflammation, promote anal fistula healing, and improve healing rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119139560A_ABST
    Figure CN119139560A_ABST
Patent Text Reader

Abstract

The invention discloses injectable hydrogel with anti-inflammatory and drainage functions for promoting anal fistula healing and a preparation method of the injectable hydrogel. The preparation method comprises the following steps: adding acrylic acid-N-succinimide ester and acrylated beta-cyclodextrin into a gelatin solution; then adding a carbon nanotube grafted with poly (vinyl benzyl trimethyl ammonium chloride), stirring and carrying out ultrasonic treatment; adding ammonium persulfate, stirring and performing ultrasonic treatment to obtain a mixture A; and heating the mixture A, cooling, washing and mechanically crushing to obtain the GAA coated CNT-g-PVBTMA hydrogel. The hydrogel is novel quaternized molecular brush grafted injectable hydrogel, has excellent swelling resistance and a broken porous structure, can effectively fill a fistula, and is beneficial to discharge of exudate; the hydrogel can also capture inflammatory cytokines of the fistula through electrostatic interaction, and shows excellent anti-inflammatory characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of medical materials, and in particular to an injectable hydrogel with anti-inflammatory and drainage functions for promoting the healing of anal fistula and a preparation method thereof. Background Art

[0002] Anal fistula is a common anorectal disease characterized by an abnormal channel connecting the anal canal / rectum and the perianal skin, leading to persistent inflammation and even an increased risk of cancer. Surgery is usually the main treatment for fistulas, with setons to ensure effective drainage. However, this approach is often difficult to perform due to the complexity of the anal fistula, and extensive dissection of the perianal sphincter may lead to long-term difficulty in healing and catastrophic incontinence, with a recurrence rate of up to 57% and an incontinence rate of up to 52%. Therefore, it is crucial to develop an effective anal fistula treatment strategy.

[0003] Current treatment options for anal fistulas include surgical setons, bioprosthetic plugs, and fibrin glue. Ideally, an elastic cord can be placed in the fistula to promote the drainage of exudate in the fistula and gradually separate the fistula from the anal sphincter using the contractile force of the elastic cord. However, the elastic cord cannot fill the fistula, exposing the affected area to inflammatory stimulation, which may promote abnormal epithelialization of the fistula wall and hinder the healing process. In addition, some materials such as bioprosthetic plugs and fibrin glue are used to fill the fistula due to their good biocompatibility and do not require extensive surgery. However, these materials hinder the drainage of exudate after filling, are more likely to cause inflammatory complications and a healing rate of 50% or less. Therefore, a balance between effective filling and adequate drainage is essential for anal fistula repair. In addition, persistent inflammatory lesions and abnormal epithelialization of the fistula are mainly caused by the accumulation of inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) in the affected area. Unfortunately, there is currently no effective clinical treatment to remove these inflammatory cytokines and fundamentally reduce the inflammation of anal fistulas. Therefore, designing anti-inflammatory materials that can provide both filling and drainage properties is highly desirable in the clinical treatment of anal fistulas and remains a huge challenge. Summary of the invention

[0004] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing an injectable hydrogel having anti-inflammatory and drainage functions and promoting the healing of anal fistula.

[0005] The second object of the present invention is to provide an injectable hydrogel prepared by the above preparation method and having anti-inflammatory and drainage functions for promoting the healing of anal fistula.

[0006] The third object of the present invention is to provide applications of the hydrogel.

[0007] The purpose of the present invention is achieved through the following technical solutions: GAA@CNT -g- The preparation method of PVBTMA hydrogel comprises the following steps: Acrylic acid N-hydroxysuccinimide ester (AAc-NHS) and acrylated β-cyclodextrin (Ac-β-CD) were added to gelatin (Gel) solution; then poly (vinylbenzyltrimethylammonium chloride)-grafted carbon nanotubes (CNT) were added. -g- PVBTMA), mixed; then added ammonium persulfate (APS), mixed to obtain mixture A; the mixture A was thermally cured to form a gel, and gelatin (Gel) / acrylic acid-N-succinimidyl ester (AAc-NHS) / acrylylated β-cyclodextrin (Ac-β-CD) doped with poly (α-vinylbenzyl) trimethylammonium grafted carbon nanotubes (CNTs) were obtained. -g- PVBTMA) hydrogel, referred to as GAA@CNT -g- PVBTMA hydrogel.

[0008] Furthermore, the gelatin solution contains gelatin and water; further, the water is deionized water.

[0009] Furthermore, the ratio of gelatin to water in the gelatin solution is 0.5-1 g:5-10 mL; furthermore, 0.8 g:7.5 mL.

[0010] Furthermore, the mass ratio of the gelatin, acrylate-N-succinimidyl ester and acryloyl β-cyclodextrin is (1-3):1:1; furthermore, it is 2:1:1.

[0011] Furthermore, the mass ratio of the gelatin, acrylic acid-N-succinimidyl ester, acryloyl β-cyclodextrin and carbon nanotubes grafted with poly(vinylbenzyltrimethylammonium chloride) is (4-12):4:4:1; furthermore, 8:4:4:1.

[0012] Furthermore, the preparation of the brominated carbon nanotubes comprises the following steps: Carbon nanotubes (CNT) are added to a mixture of HNO3 solution and H2O, mixed, stirred under reflux for reaction, and solids are collected to obtain carboxylated carbon nanotubes (CNT-COOH); carboxylated carbon nanotubes are resuspended with SOCl2 and heated and stirred for reaction, and solids are collected to obtain chlorocarbonylated carbon nanotubes (CNT-COCl); chlorocarbonylated carbon nanotubes are added with anhydrous ethylene glycol and heated and stirred for reaction, and solids are collected to obtain hydroxylated carbon nanotubes (CNT-OH); hydroxylated carbon nanotubes, CHCl3, 4-dimethylaminopyridine and triethylamine are added to a flask, and 2-bromo-2-methylpropionyl bromide dissolved in anhydrous CHCl3 is added dropwise at 0°C and under nitrogen gas, and the temperature of the flask is kept at 0°C for 3 hours and then placed at room temperature for 48 hours; Furthermore, the HNO3 solution is a 65% HNO3 solution by mass, and the ratio of the carbon nanotubes, the HNO3 solution and H2O is: 1.9 g: 58 mL: 7 mL; Furthermore, the stirring reaction under reflux is stirring under reflux at 120° C. for 27 hours; Furthermore, the ratio of carbon nanotubes to SOCl2 is 1.9 g:30 mL; Furthermore, the SOCl2 resuspended carboxylated carbon nanotubes and heated and stirred in the reaction, wherein the heating and stirring is: stirring at 70° C. for 24 h; Furthermore, the ratio of the carbon nanotubes to anhydrous ethylene glycol is 1.9 g:60 mL; Furthermore, the heating and stirring in the adding anhydrous ethylene glycol and heating and stirring the reaction is: stirring at 120° C. for 48 hours; Furthermore, the ratio of the hydroxylated carbon nanotubes, CHCl3, 4-dimethylaminopyridine and triethylamine is: 1.4 g: 35 mL: 0.1 g: 1.5 mL.

[0013] Furthermore, the preparation of the acryloyl β-cyclodextrin comprises the following steps: Add β-cyclodextrin (β-CD) to dimethylformamide (DMF); then add triethylamine, mix well and cool to 0°C; then add acrylic acid and stir to obtain a mixture B, drop the obtained mixture B into acetone to obtain a precipitate; wash the precipitate, and dry the washed precipitate to obtain acryloyl β-cyclodextrin; Furthermore, the amount of dimethylformamide added is sufficient to dissolve the β-cyclodextrin; and further, 150 mL of dimethylformamide is added for every 10 g of β-cyclodextrin; Furthermore, the ratio of β-cyclodextrin to triethylamine is 10 g:7 mL; Furthermore, the ratio of β-cyclodextrin to acrylic acid is 10 g:5 mL; Furthermore, the stirring after adding the acrylic acid is for 12 hours; Furthermore, the washing precipitate is washing the precipitate with acetone; Furthermore, the drying of the washed precipitate includes vacuum drying the washed precipitate.

[0014] Furthermore, the preparation of the carbon nanotube grafted with poly(vinylbenzyltrimethylammonium chloride) comprises the following steps: In an inert atmosphere, carbon nanotube bromide (CNT-Br), vinylbenzyltrimethylammonium chloride (VBTMA), pentamethyldiethylenetriamine (PMDETA) and dimethylformamide are mixed to obtain a uniform suspension, and stirred; under the condition of bubbling with an inert gas, cuprous bromide (CuBr) is added to the suspension, and the mixture is continuously stirred to obtain a mixture C; the mixture C is heated; diluted with a solvent, filtered and washed, and then dried to obtain CNT -g- PVBTMA; Furthermore, the inert gas is nitrogen gas; Furthermore, the brominated carbon nanotubes are subjected to ultrasonic treatment; further still, the brominated carbon nanotubes are subjected to ultrasonic treatment for 0.5 hours; Furthermore, the mass ratio of the brominated carbon nanotubes to vinylbenzyltrimethylammonium chloride is 1:14-18; furthermore, 1:16; Furthermore, the ratio of the brominated carbon nanotubes to pentamethyldiethylenetriamine is 200 mg:63 μL; Furthermore, the amount of dimethylformamide added is an amount that can uniformly mix the brominated carbon nanotubes and vinylbenzyltrimethylammonium chloride; Furthermore, in the preparation of carbon nanotubes grafted with poly(vinylbenzyltrimethylammonium chloride), the stirring is: the rotation speed is 500 to 1000 rpm, stirring for 0.5 to 1.5 hours; further, stirring for 0.5 hours, 800 rpm; Furthermore, the inert gas in the inert gas bubbling is consistent with the gas used in the previous inert gas; Furthermore, the mass ratio of the brominated carbon nanotubes to cuprous bromide is 5:(1-1.25); further still 200:43; Furthermore, the heating of the mixture C is to heat the mixture C at 60-90° C. for 10-15 hours; and further, to heat the mixture C at 75° C. for 12 hours; Furthermore, the solvent includes dimethylformamide; Furthermore, the drying comprises freeze drying.

[0015] Furthermore, the mass ratio of the acrylic acid-N-succinimide ester to ammonium persulfate is 10:(1-2); further 200:27.

[0016] Furthermore, the mixing is stirring and ultrasonicating until completely dissolved.

[0017] Furthermore, the heat curing of the mixture A into glue is to heat the mixture A at 50-70° C. for 30-60 minutes; further, the heat curing of the mixture A at 60° C. for 45 minutes.

[0018] Furthermore, the thermally curing the mixture A into glue is heating the mixture A in an oven to cure it into glue.

[0019] Furthermore, the washing is washing with deionized water.

[0020] Furthermore, the GAA@CNT -g- PVBTMA hydrogel can be mechanically broken to obtain millimeter-sized hydrogel for use; further, the GAA@CNT -g- PVBTMA hydrogel can be crushed using silicone tube to obtain millimeter-sized hydrogel for use; further, the GAA@CNT -g- PVBTMA hydrogel can be crushed into millimeter-sized hydrogel using a silicone tube with an inner diameter of 1.2 mm.

[0021] GAA@CNT -g- The PVBTMA hydrogel is prepared by the above preparation method.

[0022] GAA@CNT -g- Application of PVBTMA hydrogel in the preparation of products for treating anal fistula.

[0023] Furthermore, the product for treating anal fistula contains GAA@CNT -g- PVBTMA hydrogel; GAA@CNT -g- PVBTMA hydrogel is a millimeter-sized hydrogel.

[0024] Compared with the prior art, the present invention has the following advantages and effects: The present invention successfully developed a new type of quaternary ammonium molecular brush grafted injectable hydrogel through thermal polymerization and mechanical crushing. -g- With the addition of PVBTMA, our GAA@CNT -g-PVBTMA hydrogel exhibits excellent anti-swelling properties. Due to the broken porous structure, our GAA@CNT -g- PVBTMA hydrogel can effectively fill the fistula and promote the drainage of exudate. Notably, our hydrogel can capture inflammatory cytokines in the fistula through electrostatic interactions and exhibit excellent anti-inflammatory properties. The rat inflammatory anal fistula model confirmed that our hydrogel can effectively promote fistula healing by reducing inflammation and epithelialization. Therefore, our work provides a promising and effective treatment for the repair of anal fistula. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is GAA@CNT -g- Actual picture of PVBTMA hydrogel.

[0026] Figure 2 It is GAA@CNT -g- SEM image of PVBTMA hydrogel.

[0027] Figure 3 It is GAA@CNT -g- Pore ​​size statistics of PVBTMA hydrogel based on SEM images.

[0028] Figure 4 It is GAA@CNT -g- Rheological test results of PVBTMA.

[0029] Figure 5 It is GAA@CNT -g- Figure 2. PVBTMA penetration test results.

[0030] Figure 6 It is GAA@CNT -g- Figure 2. Inflammatory factor adsorption test results of PVBTMA.

[0031] Figure 7 It is GAA@CNT -g- Biocompatibility test results of PVBTMA.

[0032] Figure 8 GAA@CNT was used in anal fistula animal model -g- Experimental results of PVBTMA. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0034] Example 1 A method for preparing a novel injectable hydrogel for promoting anal fistula healing comprises the following steps: Synthesis of carbon nanotube bromide (CNT-Br) (the preparation of CNT-Br is the same as that in the article "Liang Y, Chen L, Zhuang D, et al. Fabrication and nanostructure control of super-hierarchical carbonmaterials from heterogeneous bottle brushes[J]. Chemical Science, 2017, 8(3):2101-2106."): CNT (1.9 g) was added to a mixture of 65% by mass HNO3 (58 mL) and H2O (7 mL). After ultrasonication for 30 min, the mixture was stirred at 120 °C under reflux for 27 h. After the reaction, filter, wash with water several times, and vacuum dry overnight at 90 ° C to obtain carboxylated carbon nanotubes (CNT-COOH); then, resuspend CNT-COOH with 30 mL SOCl2 and stir at 70 ° C for 24 h to obtain chlorocarbonylated carbon nanotubes (CNT-COCl); remove excess SOCl2 by vacuum, then add 60 mL anhydrous ethylene glycol and stir at 120 ° C for 48 h. Collect the solid by filtration and wash with tetrahydrofuran (THF), vacuum dry overnight to obtain hydroxylated carbon nanotubes (CNT-OH). CNT-OH (1.4 g), CHCl3 (35 mL), 4-dimethylaminopyridine (0.1 g) and triethylamine (1.5 mL) were added to the flask, and the flask was placed in an ice-water mixing bath. The flask was sealed and flushed with nitrogen. 2-Bromo-2-methylpropionyl bromide (0.72 mL) dissolved in anhydrous CHCl3 (15 mL) was added dropwise and the temperature of the flask was kept at 0°C for 3 hours and then at room temperature for 48 hours. The product was filtered under vacuum, washed thoroughly with CHCl3 and dried under vacuum overnight to obtain CNT-Br.

[0035] Synthesis of carbon nanotubes (CNTs) grafted with poly(vinylbenzyltrimethylammonium chloride) -g-PVBTMA): After CNT-Br was sonicated for 0.5 h, 200 mg CNT-Br, 3.2 g vinylbenzyltrimethylammonium chloride (VBTMA), 63 μL pentamethyldiethylenetriamine (PMDETA), and 20 mL dimethylformamide (DMF) were added to a 50 mL Schlenk flask to obtain a uniform suspension. The mixture was further stirred under N2 for 0.5 h. Subsequently, 43 mg cuprous bromide (CuBr) was added to the mixture and stirring was continued for another 0.5 h under N2 bubbling. Finally, the Schlenk flask was placed in an oil bath at 75 °C for 12 h. After a stepwise treatment of dilution with DMF, filtration, washing, and freeze drying, CNT-Br was obtained. -g- PVBTMA.

[0036] Synthesis of precursor material acryloyl β-cyclodextrin (Ac-β-CD): 10 g of β-cyclodextrin (β-CD) was added to 150 mL of dimethylformamide, followed by 7 mL of triethylamine. The mixture was stirred and cooled to 0 °C, and then 5 mL of acrylic acid was added to the solution. After stirring for 12 hours, the mixture was dropped into 200 mL of acetone to precipitate the modified β-CD. The precipitate was washed several times with acetone and dried in vacuum to obtain Ac-β-CD.

[0037] Hydrogel GAA@CNT -g- Preparation of PVBTMA: First, 0.8 g of gelatin was dissolved in 7.5 mL of deionized water, and 0.4 g of acrylic acid-N-succinimidyl ester (AAc-NHS) and 0.4 g of Ac-β-CD were added to the resulting gelatin solution. Then, 100 mg of CNT -g- PVBTMA and 54 mg of ammonium persulfate (APS) were added to the mixture sequentially, with stirring and ultrasonic treatment for 3-5 min after each addition. Finally, the mixture was heated in an oven at 60 °C for 45 min, cooled, washed with deionized water, and crushed using a silicone tube with an inner diameter of 1.2 mm to obtain millimeter-sized GAA@CNT -g- PVBTMA hydrogel.

[0038] Comparative Example 1 Synthesis of precursor material acryloyl β-cyclodextrin (Ac-β-CD): 10 g of β-cyclodextrin (β-CD) was added to 150 mL of dimethylformamide, followed by 7 mL of triethylamine. The mixture was stirred and cooled to 0 °C, and then 5 mL of acrylic acid was added to the solution. After stirring for 12 hours, the mixture was dropped into 200 mL of acetone to precipitate the modified β-CD. The precipitate was washed several times with acetone and dried in vacuum to obtain Ac-β-CD.

[0039] Preparation of GAA hydrogel: First, 0.8 g of gelatin was dissolved in 7.5 mL of deionized water, and 0.4 g of acrylic acid-N-succinimidyl ester (AAc-NHS) and 0.4 g of Ac-β-CD were added to the solution. Then, the mixture was heated in an oven at 60 °C for 45 min, cooled, washed with deionized water, and crushed using a silicone tube with an inner diameter of 1.2 mm to obtain millimeter-sized GAA hydrogel.

[0040] In order to verify the technical effect of the embodiment, this application uses GAA@CNT -g- PVBTMA hydrogel was used as a test sample for structural characterization and performance testing, including: 1. SEM characterization About GAA@CNT -g- PVBTMA hydrogel was photographed and tested by scanning electron microscope (SEM), and the pore size was statistically analyzed. The results are as follows: Figure 1 to Figure 3 As shown. Among them, Figure 1 For GAA@CNT -g- Physical picture of PVBTMA hydrogel; Figure 2 For GAA@CNT -g- SEM image of PVBTMA hydrogel; Figure 3 This is a graph of pore size statistics obtained through ImageJ measurement and statistics.

[0041] according to Figure 1 GAA@CNT -g- PVBTMA hydrogel has good injectability and can be formed into various two-dimensional shapes through a syringe. Figure 2 and Figure 3 GAA@CNT -g- PVBTMA hydrogel has a porous structure, which provides a physical structure for the adsorption of inflammatory factors.

[0042] 2. Rheological test About GAA@CNT -g- PVBTMA hydrogel was subjected to rheological tests using an advanced rotational rheometer (TADiscovery HR-20). Figure 4 As shown, at room temperature (25°C), the storage modulus (G') of GAA@CNT -g- The PVBTMA modulus was always higher than the loss modulus (G'') over time, indicating that the hydrogel had a stable liquid gel network at room temperature.

[0043] 3. Penetration experiment About GAA@CNT -g- PVBTMA hydrogel was subjected to liquid penetration test. We used GAA@CNT -g-The PVBTMA hydrogel was filled into a 1 mL syringe and PBS buffer was dripped into it. Figure 5 As shown, the liquid level is continuously decreasing, which simulates the scene of exudate outflow in anal fistula, indicating that our material allows exudate to continue to pass through after filling the fistula, which is crucial for the healing of the fistula.

[0044] 4. Inflammatory factor adsorption experiment Establishment of rat anal fistula model: A wire with a diameter of 1.6 mm was passed through the inner wall of the anal canal and the surrounding skin of SD rats and left in place for 28 days to form a fistula, after which the wire was cut off.

[0045] Preparation of anal fistula tissue homogenate: fresh rat anal fistula tissue was obtained from the rat anal fistula model, 1 mL of PBS was added to every 0.1 g of tissue, and the homogenate was prepared by grinding in a freezing grinder, which was diluted 10 times with PBS for subsequent experiments.

[0046] About GAA@CNT -g- PVBTMA hydrogel was used for inflammatory factor adsorption test. We injected 1g GAA@CNT -g- After PVBTMA hydrogel was co-cultured with 10 mL of anal fistula tissue homogenate for 12 hours, it was washed with PBS buffer and then immunofluorescence staining of two representative markers, TNF-α and IL-1β, was performed. -g- The PVBTMA hydrogel was replaced with 1 g of the GAA hydrogel prepared in Comparative Example 1 as a control group. Figure 6 As shown, compared with the control group, GAA@CNT -g- The PVBTMA hydrogel group absorbed more inflammatory factors, which will help reduce the inflammation of anal fistula wounds and accelerate the healing of anal fistula wounds.

[0047] 5. Biocompatibility testing Good biocompatibility of materials is very important for their application in the human body. -g- After PVBTMA hydrogel and L929 fibroblasts were co-cultured for 1, 2, and 3 days, the OD value was measured by CCK-8 reagent to determine the proliferation of cells. The co-cultivation is as follows: GAA@CNT -g- The PVBTMA hydrogels were sterilized by ultraviolet irradiation for 1 h and then immersed in culture medium for 12 h to obtain a hydrogel-culture medium mixture (so that the hydrogel content in the hydrogel-culture medium mixture was 100 mg mL -1 ). L929 fibroblasts were cultured at 8×10 3The cells were seeded on a 96-well plate at a density of 100 μL of DMEM medium containing 10% fetal bovine serum and 1% penicillin-streptomycin by mass in each well of the plate, and cultured in a humidified incubator at 37°C and 5% CO2. After incubation for 12 hours, L929 fibroblasts adhered to the culture plate, and then the DMEM medium was replaced with 100 μL of the above hydrogel medium mixture. As a control, in the step of replacing the DMEM medium, 100 μL of the above hydrogel medium mixture was replaced with 100 μL of fresh DMEM medium containing 10% fetal bovine serum and 1% penicillin-streptomycin by mass. Quantitative analysis of the CCK-8 assay showed that there was no significant statistical difference in cell proliferation between the two groups, indicating that GAA@CNT -g- PVBTMA hydrogel does not affect the proliferation of normal cells and has good biocompatibility (results as shown in Figure 7 as shown).

[0048] 6. Animal Experiment Verification GAA@CNT was then verified in SD rats. -g- The repair effect of PVBTMA hydrogel on fistula. First, a rat anal fistula model was established: a wire with a diameter of 1.6 mm was passed through the inner wall of the anal canal and the surrounding skin of SD rats and left in place for 28 days to form a fistula. After that, the wire was cut off and 0.1-0.2 mL of GAA@CNT was injected into the affected area. -g- The PVBTMA hydrogel was added to fill the fistula, the control group was injected with 0.1-0.2 mL of the GAA hydrogel prepared in Example 1 to fill the fistula, and the blank group was rinsed with 0.5 mL of saline once. The affected part of the SD rats was observed 7 days later. The results showed that compared with the blank group and the control group, the addition of CNT -g- The PVBTMA material group has a good healing function (results as shown in Figure 8 as shown).

[0049] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. GAA@CNT -g- The preparation method of PVBTMA hydrogel is characterized in that: The following steps are involved: Add acrylic acid-N-succinimidyl ester and acryloyl β-cyclodextrin to the gelatin solution; then add carbon nanotubes grafted with poly(vinylbenzyltrimethylammonium chloride) and mix well; then add ammonium persulfate and mix well to obtain a mixture A; heat cure the mixture A to obtain gelatin / acrylic acid-N-succinimidyl ester / acryloyl β-cyclodextrin doped with carbon nanotubes grafted with poly(vinylbenzyltrimethylammonium chloride), referred to as GAA@CNT -g- PVBTMA hydrogel.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the gelatin, acrylic acid-N-succinimidyl ester and acryloyl β-cyclodextrin is (1-3):1:1; The mass ratio of acrylic acid-N-succinimide ester to ammonium persulfate is 10:(1-2); The mixture A is thermally cured to form a glue by heating the mixture A at 50-70° C. for 30-60 minutes.

3. The preparation method according to claim 2, characterized in that: The mass ratio of the gelatin, acrylic acid-N-succinimide ester, acryloyl beta-cyclodextrin and carbon nanotubes grafted with poly(vinylbenzyltrimethylammonium chloride) is (4-12):4:4:

1.

4. The preparation method according to claim 1, characterized in that: The preparation of the carbon nanotube grafted with poly(vinylbenzyltrimethylammonium chloride) comprises the following steps: Under an inert atmosphere, carbon nanotube bromide, vinylbenzyltrimethylammonium chloride, pentamethyldiethylenetriamine and dimethylformamide are mixed to obtain a uniform suspension, which is then stirred; under inert gas bubbling, cuprous bromide is added to the suspension, which is then continuously stirred to obtain a mixture C; the mixture C is heated; the mixture is diluted with a solvent, filtered, washed, and then dried to obtain CNTs. -g- PVBTMA.

5. The preparation method according to claim 4, characterized in that: The brominated carbon nanotubes are subjected to ultrasonic treatment; The mass ratio of the brominated carbon nanotubes to vinylbenzyltrimethylammonium chloride is 1:14-18; The ratio of the brominated carbon nanotubes to pentamethyldiethylenetriamine is 200 mg:63 μL; The stirring is as follows: the rotation speed is 500 to 1000 rpm, and the stirring is for 0.5 to 1.5 hours; The heating of the mixture C is to heat the mixture C at 60 to 90° C. for 10 to 15 hours; The solvent includes dimethylformamide.

6. The preparation method according to claim 1, characterized in that: The preparation of the acryloyl β-cyclodextrin comprises the following steps: β-cyclodextrin is added to dimethylformamide; triethylamine is then added, mixed and cooled to 0°C; acrylic acid is then added and stirred to obtain a mixture B, and the obtained mixture B is dropped into acetone to obtain a precipitate; the precipitate is washed, and the washed precipitate is dried to obtain Ac-β-CD.

7. The preparation method according to claim 5, characterized in that: The ratio of β-cyclodextrin to acrylic acid is 10 g:5 mL; The ratio of β-cyclodextrin to triethylamine is 10 g:7 mL; The stirring after adding the acrylic acid is 12 hours. 8.GAA@CNT -g- PVBTMA hydrogel, characterized in that It is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the hydrogel according to claim 8 in preparing a product for treating anal fistula.

10. The use according to claim 9, characterized in that: The product for treating anal fistula contains GAA@CNT -g- PVBTMA hydrogel; The GAA@CNT -g- PVBTMA hydrogel is a millimeter-sized hydrogel.

Citation Information

Cited By

  • 3D printing medicine-carrying anal fistula repairing material as well as preparation method and application thereof

    CN121221857A

  • An organic nanocomposite hydrogel, its preparation method and application

    CN122664929A